2018
DOI: 10.1180/minmag.2017.081.049
|View full text |Cite
|
Sign up to set email alerts
|

Marshallsussmanite, NaCaMnSi3O8(OH), a new pectolite-group mineral providing insight into hydrogen bonding in pyroxenoids

Abstract: This is a 'preproof' accepted article for Mineralogical Magazine. This version may be subject to change during the production process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
(48 reference statements)
0
2
0
Order By: Relevance
“…Based on the latest results of X-ray diffraction (PXRD) as well as infrared (FT-IR) and Raman (FT-RS) spectroscopy methods supported by polarization and electron microscopies, it was found that chrysoprase is not a monomineral material. Instead, it is a mixture (mineral assemblage) of low-temperature SiO 2 varieties: opal, chalcedony, moganite and quartz (for details see : Sachanbiński 1980;Barsanow, Yakovleva 1984;Heflik et al 1989;Kinnunen, Malisa 1990;Plusnina, Szpila, 1990;Miehe, Graetsch 1992;Graetsch et al 1994;Origlieri 1994;Gaweł et al 1997;Göetze et al 1998;Sachanbiński et al 2001;Moxon, Rīos 2004;Sojka et al 2004;Shigley et al 2009;Graetsch 2011;Hatipoğlu et al 2011;. According to Plusnina, Szpila (1990) and Gaweł et al (1997), the transformation of low-temperature silica took place in several stages, in which gradual changes proceeded of its structure, recrystallization degree and crystal morphology.…”
Section: Mineralogy Origin and Accumulationsmentioning
confidence: 99%
“…Based on the latest results of X-ray diffraction (PXRD) as well as infrared (FT-IR) and Raman (FT-RS) spectroscopy methods supported by polarization and electron microscopies, it was found that chrysoprase is not a monomineral material. Instead, it is a mixture (mineral assemblage) of low-temperature SiO 2 varieties: opal, chalcedony, moganite and quartz (for details see : Sachanbiński 1980;Barsanow, Yakovleva 1984;Heflik et al 1989;Kinnunen, Malisa 1990;Plusnina, Szpila, 1990;Miehe, Graetsch 1992;Graetsch et al 1994;Origlieri 1994;Gaweł et al 1997;Göetze et al 1998;Sachanbiński et al 2001;Moxon, Rīos 2004;Sojka et al 2004;Shigley et al 2009;Graetsch 2011;Hatipoğlu et al 2011;. According to Plusnina, Szpila (1990) and Gaweł et al (1997), the transformation of low-temperature silica took place in several stages, in which gradual changes proceeded of its structure, recrystallization degree and crystal morphology.…”
Section: Mineralogy Origin and Accumulationsmentioning
confidence: 99%
“…In the proposal, the authors made no comparison between ‘marshallsussmanite’ and schizolite yet they knew schizolite existed as they referred to the crystal structure reported by Ohashi and Finger (1978). The crystal structure of ‘marshallsussmanite’ has not been officially published, but it is recorded in IMA proposal and can be found as a ‘preproof’ on the Mineralogical Magazine website (Origlieri et al ., 2017). Since then, Nagashima et al (2018) refined the structure of a ‘marshallsussmanite’.…”
Section: Introductionmentioning
confidence: 99%